Information for women about safety of silicone breast implants - Grigg, Martha (National Academy Press, 2000)
When the Institute of Medicine began their comprehensive study of the safety of silicone breast implants, they heard directly from many women who suffer severe systemic illnesses. While convinced that in most instances the implants were not causally related to their conditions, the committee noted that many women felt strongly that they were not provided with adequate information on which to base their decision to have these implants. This short, 16-page guide puts this vital information in simple terms for women who have had implants or are considering them. Learn the risks -- and the facts -- today.